????? ???? ??? ?????? ??? ????? ?????? ?????? ??? ???? ???? ?????? ???????? ???????? ??????? ??????? ?????? : The Influence of Word Guessing Games on the Daily Speaking Skills of Class II at Junior High School Students Maarif Singosari Malang - Erawanto, Very; Muhammad Farih (Department of Arabic Education of State Collage for Islamic Studies of Mandailing Natal, 2024)
Abstract : This research aims to determine the effect of word guessing games on the daily speaking skills of class II at junior high school students Maarif Singosari Malang. because most of the students' problems are the lack of memorizing vocabulary, so word guessing games are a good way to develop linguistic skills, especially speaking skills. This research was conducted to determine the extent of the influence of word guessing games on students' daily speaking skills. The approach used in this research is a quantitative approach and the type of research used is experimental research, and the results of the research are : 1) There is an influence of word guessing games on students' daily speaking skills of class II at junior high school students Maarif Singosari Malang, Because students' abilities are better than before. Considering the post-test result of 1550 is greater than the pre-test result of 1140. This shows the difference between the two tests, By using the T test the results were 2.83<17.943>2.08. It was found that the T test was greater than the t table and the magnitude of the effect of the word guessing game was -5.78. This has a very big influence on the use of word guessing games on students' daily speaking skills of class II at junior high school students Maarif Singosari Malang. Keywords: word guessing, speaking skill.